Differentiating autoimmune encephalitis from schizophrenia spectrum disorders among patients with first-episode psychosis. (July 2022) - Funayama, Michitaka; Koreki, Akihiro; Takata, Taketo; Kurose, Shin; Hisamatsu, Tetsuya; Ono, Atsushi; Yagihashi, Tatsuhiko; Mizushima, Jin; Yagi, Yoshikazu; Ogino, Satoyuki; Oi, Hiroki; Mimura, Yu; et al.
Abstract: Background: Although differential diagnosis between autoimmune encephalitis and schizophrenia spectrum disorders is crucial for a good outcome, the psychiatric symptoms that distinguish these two conditions have not been identified even though psychiatric symptoms are often the main manifestation of autoimmune encephalitis. Also, there are many situations in clinical psychiatry in which laboratory testing and imaging studies are not available. Because no comparative study of the psychiatric symptoms between these two conditions has been carried out, we explored diagnostically useful psychiatric symptoms in a retrospective case-control study. Methods: We recruited 187 inpatients with first-episode psychosis who were admitted to our psychiatric unit and categorized them into two groups: the autoimmune encephalitis group ( n  = 10) and the schizophrenia spectrum disorders group ( n  = 177). Differences in the symptoms and signs between the two groups were investigated. Results: Schneider's first-rank symptoms (e.g., verbal commenting hallucinations and delusional self-experience) were observed only in the schizophrenia spectrum disorders group, whereas altered perception was found more frequently in the autoimmune encephalitis group. Functional status was worse in the autoimmune encephalitis group, and neurological and neuropsychological signs were revealed almost exclusively in this group. A history of mental illness was more frequently reported in the schizophrenia spectrum disorders group than in the autoimmune encephalitis group. Conclusions: The psychiatric symptoms, i.e., Schneider's first-rank symptoms and altered perception, together with neurological and neuropsychological signs, functional status, and past history, may help clinicians accurately differentiate these two conditions among patients with first-episode psychosis. Highlights: To differentiate autoimmune encephalitis from schizophrenia, we explored diagnostically useful psychiatric symptoms in a retrospective case-control study. Schneider's first-rank symptoms (e.g., verbal commenting hallucinations and delusional self-experience) were observed only in patients with schizophrenia spectrum disorders. Altered perception were found more frequently in patients with autoimmune encephalitis.